Flow diverter stents with hydrophilic polymer coating for the treatment of acutely ruptured aneurysms using single antiplatelet therapy: Preliminary experience. Issue 5 (October 2020) - Guzzardi, Giuseppe; Galbiati, Andrea; Stanca, Carmelo; Del Sette, Bruno; Paladini, Andrea; Cossandi, Christian; Carriero, Alessandro
Background: The use of flow diverter stent (FDS) has limitations in cases of subarachnoid haemorrhage caused by ruptured aneurysm, due to the need for double antiplatelet therapy and the delay in the aneurysm occluding. The p48 MW and the p64 MW (Phenox) are available with Hydrophilic Polymer Coating (HPC), that reduces the risk of thrombus formation. Purpose of this study is to evaluate the safety and efficacy of p48 and p64 MW HPC with single antiplatelet therapy for the acute treatment of ruptured aneurysm. Methods: We retrospectively evaluated all patients treated for acutely ruptured aneurysms with a p48 MW HPC or p64 MW HPC from October 2019 to April 2020 using single antiplatelet therapy. For each patient, we considered demographic and aneurysm-related data, clinical presentation, size and location of the implanted flow diverter stent, intra- and post-procedural complications, aneurysm occlusion. Results: Seven patients were included. The ruptured aneurysms were four saccular, two blister-like and one dissecting, six in the anterior and one in posterior circulation. No intraprocedural stent thrombosis and rebleeding was observed. In two cases the aneurysm is completely excluded, in one patient it was found only neck perfusion, in three cases there were mild reduction of the sac and in one case there was a persistent perfusion. No patients needed retreatment in this series. Conclusion: In our experience, FDS HPC appears a potential treatment option in selected cases. Our study is limited by small population and short-term follow-up. We report our preliminary data, but further investigations are necessary.